IMPROVING BUDDHIST RESOURCES THROUGH DIGITAL LITERACY DEVELOPMENT IN PURWOREJO REGENCY - Sadtyadi, Hesti; Darma, Widia; Junaidi, Junaidi; Asih, Situ; Shadikah, Arina Afiyati; Sukarti, Sukarti; Harto, Sugik; Setyasih, Sri (LPPM Univ. Ibn Khaldun Bogor, 2024)
Community service was held in Purworejo Village, Central Java. The purpose of this community service is empowering and increasing Buddhist resources through the digital library development program. Community service method used is ABCD (Asset Based Community Development) approach. The result of this community service is; 1) Buddhists can better understand about digital literacy, 2) gain basic digital skills, 3) temple administrators can utilize technology for religious activities, 4) community participation in digital mastery is formed. Besides that, it has also provided welfare to the people, digital literacy and internet access have opened the horizons of information needed by people to increase insight and broadcast religion throughout indonesia, especially in Purworejo Regency.